Poles apart?: women negotiating feminity and feminism in the fitness pole dancing class - Allen, Kerry Louise (2011)
This thesis explores the current trend for pole dancing as an increasingly popular fitness activity for women, taught in health and fitness clubs across the country. With the use of participant observation in classes and in-depth qualitative interviews with women who take these classes, as well as women who teach them, I explore what these types of class mean to these women, how pole dancing classes fit into contemporary feminist debates around the nature of and the future of feminism, and the pressures and expectations placed upon women to look and act in a feminine and sexualised way. Moving beyond what I see as the quite limiting previous accounts of these classes, which have debated whether or not they are empowering or degrading for women, my research suggests that pole dancing classes are complex, may be neither empowering nor degrading, for these concepts are complicated and problematic, and that the pole dancer cannot be seen as one dimensional.